Exploring Speaking Anxiety in Debate Competitions: Students' Perspectives - Martora, Jasmal; Budidarma, Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasifik Morotai, 2024)
Debate competitions are integral to university life, fostering critical thinking and public speaking skills among students. However, they also present significant psychological challenges, notably speaking anxiety, which can hinder performance and personal growth. This qualitative study investigates the experiences of speaking anxiety among student debaters at Universitas Pasifik Morotai, focusing on triggers, manifestations, coping strategies, and the evolution of anxiety over time. Ten students of Univrsitas Pasifik Morotai who have previously taken part in National University Debating Championship (NUDC) and Kompetisi Debat Mahasiswa Indonesia (KDMI) were selected to participate in semi-structured interviews, and their responses were illustrated through thematic analysis. The findings revealed that anxiety triggers such as fear of forgetting arguments, pressure to perform, and the competitive environment were amongst the factors contributing to the students’ anxiety. Physical symptoms (e.g., rapid heartbeat), emotional distress (e.g., fear), and cognitive challenges (e.g., difficulty concentrating) were common manifestations that they experienced. Students’ anxiety coping strategies include thorough preparation, social support, and gradual exposure, leading to increased confidence and improved coping over time. These findings contribute nuanced insights into managing speaking anxiety in competitive academic settings, informing support mechanisms and educational practices.